L2 writing development : multiple perspectives - Manchón, Rosa (Trends in applied linguistics ;, 2012)
"The aim of this pioneering volume is to advance our understanding of written language learning in instructed second/foreign languageacquisition (SLA). This is achieved through a collection of empirical studies in which the contribution of diverse theoretical perspectives to our understanding of L2 writing development is explored. The volume will be of great interest to academics in the disciplines of SLA and second/foreign language (L2) writing"--Provided by publisher.